Konstruksi Portofolio Optimal Saham-Saham LQ45 Tahun 2019 di Bursa Efek Indonesia - Wibisono Hardjopranoto (Keluwih: Jurnal Sosial dan Humaniora, 2020)
Abstract—The ideal investment objective is to build an optimal investment portfolio. An investment portfolio that is able to provide maximum return at a certain level of risk. William Sharpe's (1963) Single Index Model (SIM) is a model with simple application, especially when compared to the Markowitz model (1952), mainly because of the consideration of the number of input variables. A simple SIM explains the relationship between market returns (rm) as an independent variable and returns on securities, ri with variations in the risk as the slope characteristic line, βi. The main limitation of MIS is that the risk in investing is represented only by changes in the index that are representative of the market. Using SIM, this study will describe the optimal portfolio construction by selecting LQ45 stocks on the Indonesia Stock Exchange (IDX) in 2019. The implementation of the SIM resulted in 19 LQ45 stocks selected from 45 stocks as optimal portfolio "members", along with the composition the weighting of the investment value starts from the highest weight to the lowest weight. Because using a single index in measuring risk, the application of SIM is aware of its various weaknesses and must be wise in choosing the index as the market. However, the application of SIM can provide valuable lessons for investment management.Keywords: Portfolio Analysis, Optimal Portfolio, Risk Characteristic Line, Single Index Model Abstrak—Tujuan investasi yang ideal adalah membangun portofolio investasi yang optimal. Portofolio investasi yang mampu memberikan imbal hasil (return) maksimal pada tingkat risiko tertentu. Single Index Model (SIM) William Sharpe (1963) merupakan model yang aplikasinya sederhana, terutama jika dibandingkan dengan model Markowitz (1952), terutama karena pertimbangan jumlah variabel masukannya. SIM secara sederhana menjelaskan hubungan antara imbal hasil pasar (market return, rm) sebagai variable bebas dengan imbal hasil sekuritas, ri dengan variasi perubahan risiko berupa slope characteristic line, Keterbatasan utama SIM adalah karena risiko berinvestasi hanya diwakili satu-satunya oleh perubahan-perubahan indeks tertentu mewakili pasar. Dengan menggunakan SIM, penelitian ini hendak menggambarkan bangunan portofolio optimal dengan memilih saham-saham LQ45 di Bursa Efek Indonesia (BEI) tahun 2019. Penerapan SIM dimaksud menghasilkan 19 saham LQ45 yang terpilih dari 45 saham sebagai “anggota” portofolio optimal, berikut komposisi pembobotan nilai investasinya mulai dari bobot yang tertinggi ke bobot terendah. Karena menggunakan indeks tunggal dalam mengukur risiko, penerapan SIM selain harus menyadari berbagai kelemahannya juga harus benar-benar bijak dalam memilih indeks sebagai pasarnya. Bagaimanapun, penerapan SIM mampu memberikan pelajaran yang sangat berharga bagi manajemen investasi.Kata kunci: Portfolio Analysis, Optimal Portfolio, Risk Characteristic Line, Single Index Model